Green Synthesis of Silver Nanoparticles using Coriandrum sativum and Murraya koenigii Leaf Extract and its Thrombolytic Activity - Pram, Priyanca; Mishra, Nikita; Vaithilingam, Mohanasrinivasan; Samuel, Merlyn Keziah; Mohanan, Maneesha; Kothari, Neeti; Chandrasekaran, Subathra Devi (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2024)
BackgroundPlants have been used for ages in traditional medicine, and it is exciting to perceive how recent research has recognized the bioactive compounds liable for their beneficial effects. Green synthesis of metal nanoparticles is a hastily emergent research area in nanotechnology. This study describes the synthesis of silver nanoparticles (AgNPs) using Coriandrum sativum and Murraya koenigii leaf extract and its thrombolytic activity.ObjectiveThe aim of the study was to determine the clot lysis activity of Coriandrum sativum and Murraya koenigii synthesized silver nanoparticles.MethodsLeaves of Coriandrum sativum and Murraya koenigii were collected. Methanolic extraction of the plant sample was done through a Soxhlet extractor. The methanolic extract obtained from both the leaves was subjected to GC-MS analysis. The synthesized NPs from leaf extracts were monitored for analysis, where the typical X-ray diffraction pattern and its diffraction peaks were identified. 3D image of the NPs was analysed by Atomic Force Microscopy. The surface charge of nanoparticles was identified by Zeta potential. The Clot lysis activity of Coriandrum sativum and Murraya koenigii synthesized silver nanoparticles were analysed by the modified Holmstorm method.ResultsThe thrombolytic property of the methanolic extract of plants Coriandrum sativum showed clot lysis activity at 2.5 mg/mL with 45.99% activity, and Murraya koenigii extract with 66.56% activity. The nanoparticles (Nps) from Coriandrum sativum showed clot lysis activity at 2.5 mg/mL with 58.29% activity, and NPs from Murraya koenigii with 54.04% activity. Coriandrum sativum in GC-MS exhibited 3 peaks, whereas Murraya koenigii extract showed five peaks with notable bioactive compounds.ConclusionThese NPs were further used for biomedical applications after being fixed by an organic encapsulation agent. The present research reveals the usefulness of Coriandrum sativum and Murraya koenigii for the environmentally friendly manufacture of silver nanoparticles.
Keywords: thrombolytic activity